HEAVY METAL BURDEN OF SOILS AND THEIR ACCUMULATION POTENTIALS IN SOME FOOD CROPS OF SELECTED FARMS IN KOGI STATE, NIGERIA (2014)
Heavy metal contamination in soil may be reflected in food crops due to plant uptake and such crops when consumed may cause adverse health effects. The assessment of toxic metal burden of soils and the capacity of food crops to accumulate these metals are essential. Such studies have not been reported in literature for Kogi State, a state noted for intense agricultural activity. The aim of this study was to determine heavy metals in soils, food crops, irrigation waters and sediments of dam of selected farms in Kogi State and also metals uptake potentials and toxicity threshold limits in crops. Soils and plants from nine major farms, three from each senatorial district, and a control site (another farm), were randomly sampled quarterly from May, 2007 to February, 2009. Thirty-two soil samples were obtained from 0-15 and 15-30 cm depths in each farm and control site, to make 320 composite samples. A total of 640 plants samples (leaves and edible parts each of pumpkin 64, passion fruit 96, maize grain 96, sugar cane stem 64 and tubers of cassava 320) were collected. Fifty-six samples of each of irrigation waters and sediments were collected. Soils, water and sediments were each digested with HNO3 while 3:1 HNO3:HClO4 was used to digest the crops. Digests were analysed for Cd, Co, Cu, Ni, Pb and Zn by atomic absorption spectrophotometry. Speciation of metals in soil was done by Tessier sequential extraction procedure and soil-plant transfer factor was determined as the ratio of metal concentration in plants to soil. A soil-plant equilibrium model (STRATA) was used to analyse soil-plant metal data in order to obtain crop uptake characteristics and toxicity threshold limits. Data were analysed using ANOVA at p = 0.05. The mean concentrations of Cd, Co, Cu, Ni, Pb and Zn in top soils were 0.6±0.7, 5.4±3.9, 4.3±2.3, 15.7±9.2, 11.8±6.1 and 26.0±17.0 mg/kg respectively, while subsoil values were 0.7±0.7, 5.0±3.3, 3.9±2.1, 14.6±8.3, 11.7±5.4 and 25.0±14.0 mg/kg respectively. These did not vary significantly among farms. Proportions in non-residual soil phases were 82.6% Cd, 48.6% Co, 72.5% Cu, 73.2% Ni, 41.9% Pb, and 84.3% Zn. Mean concentrations (mg/kg) in edible crop parts were: Cd 0.5±0.1, Co 4.4±3.0, Cu 4.4±0.2, Ni 25.5±9.2, Pb 0.2±0.1 and Zn 20.1±1.3. Nickel levels in cassava tubers and leaves iv (34.5±19.0 and 29.0±16.0 mg/kg respectively) were significantly higher than in the control (3.1±0.5 mg/kg) and exceeded Chinese standard limit of 10 mg/kg. Metals levels in water and sediments were within standard limits of 0.001-3.0 and 6.0-25.0 (mg/kg) respectively. Soil-plant transfer factors indicated low accumulation into crops. Transfer factors for Cd, Co, Cu, Ni, Pb and Zn in maize grain were: 0.4, 0.01, 0.6, 1.9, 0.02, and 1.2 respectively, and in tubers were: 0.4, 0.01, 1.8, 2.5, 0.01 and 0.7 accordingly. Metal concentrations in crops parts were generally lower than model-derived threshold limits for toxicity in plants. There was no heavy metal contamination in investigated food crops except nickel in cassava. Therefore, the soil may not require any form of remedial action. Keywords: Heavy metals in food crops, Soil and sediment contamination, Metal uptake, Metal speciation, Toxicity in plant. Word count: 497